Could elective nodal irradiation for locally advanced rectal cancer be omitted in the context of total neoadjuvant therapy? An analysis of the recurrence sites of rectal cancer - Xiao, Linlin; Zhuo, Shiyu; Gao, Yuanhang; Sun, Jingyi; Xiao, Yuting; Wang, Lu; Wang, Xuan; Qu, Fuyin; Liu, Ming; Wang, Yi; Gao, Chao; Wang, Jun; et al. (Frontiers in Oncology, 2024)
PurposeThis study aims to optimize neoadjuvant radiotherapy target area for locally advanced rectal cancer (LARC) patients undergoing total neoadjuvant therapy (TNT) by examining local recurrence patterns.Methods and materialsWe retrospectively analyzed the clinical data of rectal cancer patients who undergone local recurrence after surgery. Recurrence sites were categorized and compared with initial diagnosis imaging, focusing on visible and suspicious lesions.ResultsOf the 126 patients who met our criteria, 186 lesions were analyzed. Within these, 75.40% of cases (95/126) and 83.33% of lesions (155/186) were located within the pelvic cavity. Conversely, 3.97% of cases (5/126) and 3.33% of lesions (6/186) occurred outside the pelvic cavity. Additionally, 20.63% of cases (26/126) and 13.44% of lesions (25/186) were found in both regions. Recurrences were predominantly observed in mesenteric regions (MR) (40.86%, 76/186) and presacral regions (PR) (32.26%, 60/186). In addition, 86.51% of patients (109/126) had recurrent lesions in HRA and the suspected lesions areas. Further analysis showed that initial CEA levels and adjuvant therapy types were identified as independent predictors for recurrence in MR/PR and initially suspected lesions. 86.51% of patients had recurrent lesions in HRA and the suspected lesions areasConclusionThe MR, PR, and areas of initial suspicious lesions are high-risk zones for post-surgical recurrence of LARC. Exploratory study of involved-field irradiation (IFI) can be carried out in the context of TNT in LARC.